Etoposide (VP-16-213)-induced gene alterations: potential contribution to cell death. - Berger, N A (1991)
We have shown previously a good correlation between etoposide-induced sister chromatid exchanges (SCE) and cytotoxicity. A semisynthetic derivative of podophyllotoxin, etoposide is also called Vepesid (Bristol; code designation VP-16-213, abbreviated VP-16). Since SCE represent DNA recombinational events, we hypothesized that VP-16-induced SCE might result in nonhomologous recombination in which segments of DNA were either deleted or added, leading to an alteration of gene sequences responsible for essential cell proteins. Alterations of such essential genes and consequent interference with formation of their products could consequently lead to cell death. To evaluate whether VP-16 treatment caused sufficient levels of DNA sequence alterations to interfere with gene product formation, we isolated hypoxanthine (guanine) phosphoribosyltransferase (HPRT)-deficient mutants from Chinese hamster V79 cells grown in the presence or absence of VP-16. DNA from 3 spontaneous mutants and 10 VP-16-induced mutants was analyzed by Southern blot hybridization to a full-length hamster HPRT cDNA probe. Most of the VP-16-induced mutants showed partial deletions and/or rearrangements of the HPRT gene. In contrast, spontaneous mutants showed negligible deletions or rearrangements. These results provide strong support for our hypothesis that deletion of genetic sequences may constitute an important component of the mechanism of VP-16-induced cell death.